2016
DOI: 10.1007/s00253-016-7354-6
|View full text |Cite
|
Sign up to set email alerts
|

New tools for chloroplast genetic engineering allow the synthesis of human growth hormone in the green alga Chlamydomonas reinhardtii

Abstract: In recent years, there has been an increasing interest in the exploitation of microalgae in industrial biotechnology. Potentially, these phototrophic eukaryotes could be used for the low-cost synthesis of valuable recombinant products such as bioactive metabolites and therapeutic proteins. The algal chloroplast in particular represents an attractive target for such genetic engineering, both because it houses major metabolic pathways and because foreign genes can be targeted to specific loci within the chloropl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
99
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 92 publications
(102 citation statements)
references
References 60 publications
0
99
0
Order By: Relevance
“…As illustrated in Fig. 1, this results in marker-free transformants in which the only foreign DNA in the plastome is the gene of interest [27,28]. Expression of the gene is achieved by fusing the coding sequence to promoters and untranslated regions from highly expressed endogenous genes, such as the photosynthesis genes psaA and psbA.…”
Section: The Algal Chloroplast As a New Bio-factorymentioning
confidence: 99%
See 1 more Smart Citation
“…As illustrated in Fig. 1, this results in marker-free transformants in which the only foreign DNA in the plastome is the gene of interest [27,28]. Expression of the gene is achieved by fusing the coding sequence to promoters and untranslated regions from highly expressed endogenous genes, such as the photosynthesis genes psaA and psbA.…”
Section: The Algal Chloroplast As a New Bio-factorymentioning
confidence: 99%
“…These include hormones such as human growth hormone [28], anti-hypertensive peptides [45], cancer therapeutics [46], antibody mimics [47], autoantigens [48], wound-healing factors [47] and anti-bacterial enzymes [31]. These examples serve to illustrate the potential of the chloroplast as a platform for a wide variety of recombinants.…”
Section: Other Therapeutic Proteinsmentioning
confidence: 99%
“…Wannathong et al. used glass beads for the transformation of algal chloroplast and reported that recombinant human growth hormone could be stably expressed up to 25 μg/mL. In another study, Castellanos‐Huerta et al.…”
Section: Various Products From Transplastomic Algaementioning
confidence: 99%
“…Introduction of three gene cassettes into the C. reinhardtii plastome using a combinatorial approach. Design of the cassettes, chloroplast transformation and analysis of transformant lines were carried out using the methods described previously [24,30]. (a) The transformation plasmid pICS is derived from the expression vector pASapI and was assembled using three transgene cassettes in which each coding sequence (ibv-ctb, codA and splB) was codon-optimised and extended to encode a C-terminal HA tag.…”
mentioning
confidence: 99%
“…As shown in Fig. 1a, the first three genes were assembled into a single plasmid (pICS) that is based on the chloroplast expression vector pASapI [30]. Details of this vector and the cloning strategy used are given in the supplementary data (available in the online version of this article).…”
mentioning
confidence: 99%